Superior oxidation resistance in air during hot stamping of a coating-free press-hardened steel achieved by pre-oxidation - Zhao Li; Lingyu Wang; Zhou Wang; Jianfeng Wang; Wei Xu (Journal of Materials Research and Technology, 2024)
While coating-free press-hardened steel (CF-PHS) can prevent high-temperature oxidation during hot stamping, it requires high-purity nitrogen protection, which increases the operation cost. This study presents a novel pre-oxidation treatment that significantly enhances the air oxidation resistance of CF-PHS. By investigating three distinct pre-oxidation temperatures (640, 760, and 840 °C), two crucial characteristics of pre-oxidation are identified. The formation of a higher proportion of Mn-oxides and Mn–Fe spinel during the pre-oxidation process improves the compactness of the oxide film. Additionally, the continuous Mn–Cr spinel layer reinforces this compactness, thereby anticipated to facilitate the formation of a protective Cr2O3 film during hot stamping in air. Notably, the 760 °C pre-oxidized CF-PHS exhibits exceptional oxidation resistance after hot stamping in air, attributable to the above characteristics and the absence of significant Cr- and Mn-depletion in the subsurface. However, excessive pre-oxidation may adversely affect the oxidation resistance of the CF-PHS. The present study not only offers a cost-effective approach to enhancing the oxidation resistance of the CF-PHS but also contributes to the understanding of their antioxidant mechanisms.